ANALISIS PEMODELAN RISIKO KEBAKARAN HUTAN DAN LAHAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (Studi Kasus di Kabupaten Paser, Kalimantan Timur) - , MEDITA HERMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A negative effect of forest and land fire could cause many losses and also blocking the goal of development. Therefore, those impacts need to be minimized with various efforts that formulated carefully. The study of vulnerability and risks introduced by the IPCC (International Governmental on Climate Change) in 2007 was the initial step in order to provide an illustration and way of thinking about how to formulate strategy to reduce the negative impact on climate change. This research attempt to analyze hazards, vulnerabilities, capacities, and the risk of forest fires and land at regency scale using two different formula, the formula of the IPCC that has been applied by the KLH (Ministry of Environment) and formula that have been modified by the BNPB (National Disaster Management Agency). The vulnerability is generally defined as a function of exposure (E), sensitivity (S) and capacity for adaptation (AC) against the dangers of climate change in a relationship V = f . While risk assessment (R) is a function of danger (H) and vulnerability (V) relation R = f . The result will be analyzed on how efforts can be made in order to reduce the negative impact of land and forest fire hazards and climate in this case. The results showed that the study of vulnerability and risk assessment can be used to determine distribution area that has the level of hazard, vulnerability, and risk of forest fires and land in the form of a map. A map that produced through a modification of the formula BNPB is better used in Indonesia because the determination and details of the criteria and indicators to assess weights and classes. It does not mean that the formula of IPCC is not good to be used, because until now there are no institution or research that can determine those criteria and indicators.